Channels of Power : The UN Security Council and U.S. Statecraft in Iraq - Thompson, Alexander, 1972- (Book collections on Project MUSE., 2009)
Thompson surveys U.S. Policy toward Iraq, starting with the Gulf War, continuing through the interwar years of sanctions and coercive disarmament, and concluding with the 2003 invasion and its long aftermath. He offers a framework for understanding why powerful states often work through international organizations when conducting corercive policies and why they sometimes choose instead to work alone or with ad hoc coalitions. Because having legitimacy for their actions is important for normative reasons, states seek multilateral approval. Rationalist alternative to these standard legitimation arguments is offered. One is based on the notion of strategic information transmission: When state actions are endorsed by an independent organization, this sends politcally crucial information to the world community and results in greater international support -- Publisher description.